Desvaneciendo ilusiones : las enfermedades, las vacunas y la historia olvidada - Humphries, Suzanne; Bystrianyk, Roman (Octaedro, 2015)
Starting in the mid-1800s, there was a steady drop in deaths from all infectious diseases, decreasing to relatively minor levels by the early 1900s. The history of that transformation involves famine, poverty, filth, lost cures, eugenicist doctrine, individual freedoms versus state might, protests and arrests over vaccine refusal, and much more. But the authors shows that vaccines, antibiotics, and other medical interventions are not responsible for the increase in lifespan and the decline in mortality from infectious diseases.